Borax and Boric Acid Combination As Fire Retardant and Anti-termite Agents on Red Meranti Wood - Mahdi Santoso; Sutjipto A. Hadikusumo; Abdul Aziz (Jurnal Ilmu Kehutanan)
Woods have properties which are easy to be ignited by fire and most of them have a low natural durability. Therefore, it is required to improve the quality of wood by impregnating the fire-retardant and anti-termites possessed chemicals. The aim of this research was to investigate the effect of impregnation duration by combination of borax:boric acid ( 1:1) against the fire and termites. This study used red meranti wood (Shorea spp) with the dimension of 6 x 15 x 500 cm. The pressure times were 1, 2, and 3 hours as the concentration of borax:boric acid was 7% in 5 replications. Empty cell method was applied as preservation method by 12 kg/cm2 of pressure. Testing the fire resistance referred ASTM E 69-02 B and anti-termite evaluation was conducted by no-choice feeding method. Observed parameters were absorption, actual retention, burn intensity, maximum combustion temperature, glowing time, termite mortality, mass loss, the degree of damage and visual observation. The results showed that the combination of borax: boric acid (1: 1) could improve the quality of red meranti samples against the fire and termite attacks. The most effective impregnation process were 2 hours of pressing time to obtain the 331 kg/ m3 of absorption; actual retention of 28.8 kg/ m3; burnt intensity of 10.9%; maximum combustion temperature of 140ºC; glowing time of 1.03 minutes, termite mortality of 100%; mass loss of 0.002%; and mild degrees of damage category.